Addressing Psychoactive Drug Use in Iraq: Embracing Challenges and Seizing Opportunities - Al Janabi, Taysir (AL-Kindy College Medical Journal, 2024)
Drug use disorder is a global health issue and one of the leading causes of premature deaths and disability. There is an increase recognition of the need for a public health rather than criminal justice approach to mitigate the current health burden and prevent future health loss